(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study explored the predictors of adherence to government prevention strategies for COVID-19 in Calabar Municipal, Cross River State, Nigeria. The study utilized a survey questionnaire to collect data on adherence to government COVID-19 preventive measures, as well as demographic factors that could potentially influence adherence. Data analysis was conducted using the One-way analysis of variance and multiple regression. The findings show only sex was significantly correlated with compliance with COVID-19 prevention measures. However, a composite analysis reveals that adherence to government COVID-19 prevention efforts is predicted by sociodemographic factors, including age, sex, occupation, religion, and educational attainment. Furthermore, people were more inclined to follow preventive measures if they were older, female, civil servants, Muslims, and had a tertiary education. These results demonstrate the necessity of tailored interventions that consider the unique predictors of adherence in Calabar Municipal, Cross River State, Nigeria. The study recommends that by adopting a holistic and context-sensitive strategy, it is possible to improve adherence to disease preventive measures, ultimately contributing to better public health outcomes in Calabar Municipal and similar communities.